Perekonomian era pandemi covid-19 - SASMITA, ZAHRA HERDINATA (Maliki Interdisciplinary Journal, 2026)
This research was conducted to identify: (1) the impact of the covid-19 pandemic on the economy, (2) the policy responses implemented, and (3) recovery efforts. This study employs a literature review approach using a descriptive qualitative method, focusing on the collection, analysis, and presentation of data from written sources. The results indicate that, overall, the covid-19 pandemic—which began in late 2019—caused global and national economic contractions, including in indonesia, characterized by negative gdp growth in 2020. The pandemic slowed economic momentum to the point of triggering economic crises both domestically and globally. Consequently, various sectors, ranging from small businesses to large-scale industries, experienced a decline, prompting the government to issue various policies and legal strategies (politik hukum) to restore economic conditions. Different countries implemented unique strategies to anticipate these challenges. The application of legal-political policies varied, with some implementing full lockdowns while others opted for micro-lockdowns. These regulations are vital as a strategic foundation for economic recovery policies aimed at boosting more stable growth. The choice of legal-political policies in recovery efforts can serve as a "problem-solving" mechanism through the lens of the economic constitution. Empirically, economic recovery plays a pivotal role as the backbone of public welfare, as mandated by the constitution. The design of regulations in economic recovery efforts serves the critical purpose of creating prosperity.